Abundant Expression of Lysyl Oxidase-like 2 Protein in Intrahepatic Bile Ducts of Infants With Biliary Atresia. Issue 3 (September 2019) - Honigbaum, Stefany; Zhu, Qingfeng; Layman, Andrew; Anders, Robert A.; Schwarz, Kathleen B.
ABSTRACT: Introduction: Biliary atresia (BA) is characterized by rapidly progressive inflammation and fibrosis of the biliary tract, which usually progresses despite surgical intervention (Kasai hepatoportoenterostomy). Lysyl oxidase-like (LOXL2) is an extracellular matrix enzyme that catalyzes the cross-linking of fibrillar collagen and elastin and is thought to play a crucial role in tissue fibrosis; anti-LOXL2 drugs have been shown to be antifibrotic in animals. Objective: The aim of the study was to investigate the presence of LOXL2 in BA livers and hepatic and extrahepatic control tissues. Methods: Liver wedge biopsies from infants with BA (n = 20) were obtained at Kasai, and were compared with non-BA livers (n = 20). Liver fibrosis was scored using the Ishak scale, and immunohistochemistry was performed using a commercially available polyclonal anti-LOXL2 antibody. The expression of LOXL2 was scored for intensity and for distribution of bile duct staining by a pathologist blinded to the diagnosis. Staining of LOXL2 in pediatric control tissue, muscle (n = 5), heart (n = 5), and bone (n = 10) was performed. Results: Tissue from patients with BA abundantly expressed LOXL2 (intensity score 2.0 vs 1.4 [ P  ⩽ 0.001]) for non-BA and distribution of bile duct-staining score of 3.0 versus 2.8 ( P  = 0.001) for non-BA. Fibrosis score of all BA samples was 4.2 versus 3.1 for non-BA. Nonhepatic pediatric tissue displayed minimal to no LOXL2 staining. Conclusions: There is significant overexpression of LOXL2 in BA hepatic tissue with minimal expression in extrahepatic tissue. The over expression noted in human hepatic tissue at Kasai suggests the rationale for further investigation of anti-LOXL2 therapeutics in BA. Abstract : Supplemental Digital Content is available in the text